2018
DOI: 10.2478/bjmg-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the PPARD gene expression level changes in football players in response to the training cycle

Abstract: The PPARD gene codes protein that belongs to the peroxisome proliferator-activated receptor (PPAR) family engaged in a variety of biological processes, including lipid metabolism in muscle cells. In this study, we assess the relationship between PPARD gene expression lipid metabolism parameters and the variation of the PPARD gene expression before (T1) and after 12 hours of training (T2) sessions in a group of football players. Peripheral blood lymphocytes were obtained from 22 football players (17.5±0.7 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Firstly PPARD is a regulatory factor for the expression of enzymes needed in fat metabolism, which enhances the activity of PPARD to increase the expression of various enzymes, thus increasing fat metabolism and energy consumption [24]. Secondly, PPARD regulates the body's fat metabolism and is a sensor of plasma-free fatty acids in the liver [25]. Thirdly, PPARD is closely related to fat metabolism and cell proliferation, cell differentiation, migration, apoptosis, and in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly PPARD is a regulatory factor for the expression of enzymes needed in fat metabolism, which enhances the activity of PPARD to increase the expression of various enzymes, thus increasing fat metabolism and energy consumption [24]. Secondly, PPARD regulates the body's fat metabolism and is a sensor of plasma-free fatty acids in the liver [25]. Thirdly, PPARD is closely related to fat metabolism and cell proliferation, cell differentiation, migration, apoptosis, and in ammation.…”
Section: Discussionmentioning
confidence: 99%
“…Mice studies suggested that PPARδ plays an important role in myelination of the corpus callosum, cell differentiation, epidermal cell proliferation, and lipid metabolism [20–22]. Functional studies suggested that the PPARD gene was involved in muscle development and adaptive response to fitness training [23–26]. In mice skeletal muscle, targeted expression of activated PPARδ triggered adaptation from type 2 muscle fibers to type 1 muscle fibers [27].…”
Section: Introductionmentioning
confidence: 99%